RELA mRNA Expression in Epithelial Ovarian Cancer: Correlation with rs11820062 Gene Variant: Ekspresi mRNA RELA pada Kanker Ovarium Epitelial : Korelasinya dengan Varian Gen rs11820062 - Ria Kodariah; Dewi Sukmawati; Luluk Yunaini; Primariadewi Rustamadji; Benedikta D. Saraswati; Dwi A. Suryandari; Puji Sari (Indonesian Socety of Obstetrics and Gynecology, 2023)
and its correlation to i mRNA expression in low-grade and high-grade EOC’s patients from Dr. Cipto Mangunkusumo General hospital, Indonesia. Methods: This study is cross-sectional with a total of 65 healthy subjects and 80 ovarian biopsies (15 ovarian cysts as expression calibrators, 36 low-grade EOC, and 29 high-grade EOC) were used in this study. The distribution of genotypes and alleles was analyzed using ARMS PCR. The mRNA expressions of RELA were determined by real-time polymerase chain reaction (qPCR) analysis.Results: There was no significant difference between genotype and allele distributions for RELA rs11820062 in normal and case group. RELA relative mRNA expression was significantly higher in low-grade and high-grade EOC compared to in ovarian cysts (p<0.01). RELA rs11820062 CC genotype correlated to higher RELA mRNA relative expression and the TT genotype of RELA rs11820062 correlated with lower RELA mRNA relative expression in low-grade and high-grade EOC.Conclusion: C allele in rs11820062 caused an increased expression of RELA mRNA, which individuals with CC genotype correlated with higher RELA expression in low-grade and high-grade EOC. In contrast, individuals with the T allele of RELA rs11820062 had a protective effect against EOC risk because the RELA TT genotype tended to have a lower RELA mRNA expression in EOC.Keywords: epithelial ovarian cancer, NF-kB, RELA, rs11820062.AbstrakTujuan: Mengetahui distribusi RELA rs11820062 dan korelasinya dengan ekspresi mRNA RELA pada pasien EOC low-grade dan high-grade di Rumah Sakit Dr. Cipto Mangunkusumo, Indonesia.Metode: Penelitian ini merupakan peneliatan potong lintang terhadap 65 sampel darah perempuan normal dan total 80 biopsi kanker ovarium dengan rincian: 15 kista ovarium sebagai kalibrator ekspresi, 36 EOC low-grade, dan 29 EOC high-grade. Distribusi genotipe dan alel dianalisis menggunakan ARMS PCR dan ekspresi mRNA RELA dikuantifikasi menggunakan teknik qPCR. Hasil: Tidak terdapat perbedaan distribusi genotipe dan alel antara kelompok normal dengan kasus EOC. Ekspresi relatif mRNA RELA meningkat secara signifikan pada kelompok EOC low-grade dan high-grade. Individu dengan genotipe RELA rs11820062 homozigot CC memiliki ekspresi mRNA yang lebih tinggi dibandingkan genotipe lain. Sebaliknya individu dengan genotipe TT memiliki korelasi dengan ekspresi mRNA RELA yang lebih rendah pada tipe low-grade dan high-grade EOC. Kesimpulan: Alel C pada RELA rs11820062 menyebabkan peningkatan ekspresi mRNA RELA pada pasien EO yang dilihat dari individu dengan genotipe CC cenderung memiliki ekspresi mRNA RELA yang lebih tinggi pada tipe EOC low-grade dan high-grade. Sebaliknya, individu dengan alel T RELA rs11820062 diduga memiliki efek protektif terhadap risiko EOC karena adanya korelasi antara genotipe TT dengan ekspresi mRNA RELA yang lebih rendah pada EOC.Kata kunci: kanker ovarium epitelial, NF-kB, RELA, rs11820062.